2013
DOI: 10.1111/ijac.12210
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis of Si‐doped Hydroxyapatite Nanopowders: Mechanical and Bioactivity Evaluation

Abstract: Si‐doped hydroxyapatite nanoparticles (n‐SixHA) were prepared by hydrothermal synthesis from calcium nitrate tetrahydrate and diammonium hydrogen orthophosphate. A rod‐like morphology was obtained for all the powders irrespective of the incorporated Si‐doping level. But the crystallinity of the n‐SixHA powders, the density achieved upon sintering powder compacts and their mechanical properties (three‐point‐bending strength), as well as their biomineralization activity evaluated by immersing them into simulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…(4a)) [39]. The presence of oxygen ions results in the distortion of the hexagonal symmetry of HA, which results in the formation of energetically unstable material that decomposes into β-TCP during the calcination process [40]. The use of lower calcination temperature and absence β-TCP as a secondary phase in XRD patterns confirmed that the mechanism proposed in Eq.…”
Section: Resultssupporting
confidence: 57%
“…(4a)) [39]. The presence of oxygen ions results in the distortion of the hexagonal symmetry of HA, which results in the formation of energetically unstable material that decomposes into β-TCP during the calcination process [40]. The use of lower calcination temperature and absence β-TCP as a secondary phase in XRD patterns confirmed that the mechanism proposed in Eq.…”
Section: Resultssupporting
confidence: 57%